2022
DOI: 10.1186/s12904-022-00935-2
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care training: a national study of internal medicine residency program directors in the United Arab Emirates

Abstract: Background Internal medicine residents are responsible for providing much of the direct care for palliative and terminally ill patients in teaching hospitals in the United Arab Emirates (UAE). To date, little systematic information is available on the prevalence of palliative care (PC) programs or faculty in UAE academic hospitals, or on the nature of PC education in internal medicine residency programs in the country. Methods Semi-structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…End-of-Life Care (EoLC) is culturally and contextually relevant, and has received substantial interest among researchers and industry practitioners. Many countries have promoted the implementation of EoLC, to varying degrees, according to their economic status, resources, and energy [ 1 , 2 , 3 , 4 , 5 ]. Literature review studies have been accepted as an effectual means to map the existing intellectual territory [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…End-of-Life Care (EoLC) is culturally and contextually relevant, and has received substantial interest among researchers and industry practitioners. Many countries have promoted the implementation of EoLC, to varying degrees, according to their economic status, resources, and energy [ 1 , 2 , 3 , 4 , 5 ]. Literature review studies have been accepted as an effectual means to map the existing intellectual territory [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent studies in UAE medical schools and residency programs, lack of trainee awareness and interest in PC were cited as major barriers to PC education [ 11 , 39 ]. Our findings, however, show high student interest in PC training, with over 95% of medical student respondents reporting that it was important to learn about PC, and 95% requesting additional PC training during residency.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the challenges of PC that have been consistently addressed in the literature state that PC is not sufficiently integrated in nursing and medical curricula in the region, and even in affluent countries, most caregivers have received little or no PC training. 17 A recent study 11 in the United Arab Emirates revealed a lack of structured PC training and limited provision of formal teaching and assessment of trainee knowledge and skills in palliative and EOL care.…”
Section: Introductionmentioning
confidence: 99%